(untitled) (Research, Society and Development, 2020)
The use of medicinal plants to treat health problems has been going on since ancient times and remains very current. The barks of Mimosa caesalpiniifolia, popularly known as “sabiá”, are used in home medicine for healing, bronchitis, among others. The objective of the present study was to qualitatively and quantitatively evaluate the secondary metabolites present and the antioxidant activity of leaf, twig and bark extracts of Mimosa caesalpiniifolia in different solvents. The presence of several metabolites was verified, among them: phenols, anthocyanins, steroids and catechins. In addition, high concentrations of tannins were found in its leaves (1471 mg/L). Extracts also showed great antioxidant activities for the two methods of radicals used. The ethanolic extract of the branches (7.08 mg/L) and the aqueous extracts of the barks (9.38 mg/L) presented IC50 close to the trolox standard (4.0 mg/L) in DPPH method. ABTS test showed the ethanolic extracts twigs (2658.57 µmol/Ltrolox/g extract) and bark (2314.81 µmol/Ltrolox/g extract) with significant values. Results indicates that the species has a good potential for use in the pharmacological area.